2016
DOI: 10.1149/2.0011610jss
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anisotropic Thermal Stress on Behavior of Grown-In Defects during Si Crystal Growth from a Melt

Abstract: Anisotropic thermal stress near the melt/solid interface during growth of a Si crystal from a melt significantly affects control of grown-in defects when the diameter of the growing crystal is large. This effect on the behavior of intrinsic point defects in a growing Si crystal with 300-mm diameter was investigated by calculations and experiments. One has to take into account this effect in the development of a crystal-pulling process for 450-mm-diameter defect-free Si crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…13) Sueoka et al and Kamiyama et al introduced the thermal stress effect on the point defect simulation, wherein the concentration distributions of V and I in the crystal during the growth process were calculated by solving the advection diffusion equation and considering the pair annihilation of V and I. 14,15) On the other hand, Abe et al put a unique interpretation on the determination of defect type V-or I-dominant from the experimental data, i.e. the growth interface is filled with only vacancies, and self-interstitials are generated when the thermal stress exceeds a critical value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13) Sueoka et al and Kamiyama et al introduced the thermal stress effect on the point defect simulation, wherein the concentration distributions of V and I in the crystal during the growth process were calculated by solving the advection diffusion equation and considering the pair annihilation of V and I. 14,15) On the other hand, Abe et al put a unique interpretation on the determination of defect type V-or I-dominant from the experimental data, i.e. the growth interface is filled with only vacancies, and self-interstitials are generated when the thermal stress exceeds a critical value.…”
Section: Introductionmentioning
confidence: 99%
“…16,17) However, in these reports of Sueoka et al [8][9][10][11][12] and Nakamura et al 13) the point defect behavior due to thermal stress was confirmed by the change in ξ cri . In the studies by both Kamiyama et al 14) and Sueoka et al 15) it was difficult to verify the impact of stress effect on point defect behavior. This was because of the low stress conditions and no comparison between experimental and simulation grown-in defect patterns in Sueoka's study 15) and due to the discrepancy between the actual crystal-melt interface shape and the simulation in Kamiyama's study.…”
Section: Introductionmentioning
confidence: 99%
“…Stress changes PD formation enthalpy, affecting the equilibrium concentration and the critical value of v/G, which has been confirmed experimentally [18] and explained theoretically [19]. Since the stress generally increases with the crystal size, this effect is more important for large crystals and is actively investigated nowadays [20][21][22][23].…”
Section: Introductionmentioning
confidence: 68%
“…While the PD parameter sets proposed by different groups are validated and finetuned to improve agreement with experiments in the body phase [3,4,20,[23][24][25][26] (we are not aware of works comparing simulation results with experiment in the cone), they vary considerably. One of the possible reasons for such discrepancies is uncertainties in the global heat transfer (e.g., due to imprecise material properties) since the point defect distribution is sensitive to the temperature field in the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the mass production of large-diameter defect-free CZ-Si crystals, one must account for the effect of thermal stress on intrinsic point defect properties. [8][9][10]28 This is because the defect-free region just outside the OSF-ring moves due to the slight increase in V concentration caused by the compressive thermal stress.…”
Section: Simulation Of Point Defect Distribution In Growing Cz-si Cry...mentioning
confidence: 99%